CYCLOSTRATIGRAPHY OF UPPER PALEOZOIC TERRIGENOUS DEPOSITS IN THE TAIMYR PENINSULA - Shishlov S.B. (My University, 2003)
Combination of sedimentological and cyclostratigraphic methods is used to depict for the first time the relative sea-level fluctuations characterizing a series of sections of Upper Paleozoic terrigenous deposits in the Taimyr Peninsula. As a result, seven transgression-regression cycles of the fifth order (magnacycles) are distinguished. According to their position in sections, paleontological characteristic, and changes in lithology and facies types, the cycles are identifiable throughout the region. Thus, the established magnacycles can be regarded as natural regional geohistoric units useful for elaboration of a new stratigraphic scheme for the Upper Paleozoic in the Taimyr Peninsula.
Keywords: Paleozoic; Paleozoic; Палеозой